A Comprehensive Study of Dental Materials and Their Toxic Ingredients Associated With Neuro-Cutaneous Syndrome (NCS) and Morgellons, with Notes on Research Background - Omar M. Amin (Morgellon’s Disease and Neurocutaneous Syndrome (NCS): Cases and Recovery, 2021)
Neurocutaneous Syndrome (NCS) and Morgellons were recently described from many patients showing dermatological and neurological disorders. Of the many different possible exposures, the most common were dental materials, especially sealants, liners, bases, cements, adhesives, bonding agents, metals, crowns, and root canal materials. The role of these dental materials as the causative agents of NCS was verified by the application of the cause-effect relationship. The original listing included about 360 products that were originally reported in a previous publication by the same author (Amin, 2005). The present work includes a considerably more extensive listing of 644 products. It is recommended that dentists research MSDS sheets for proposed dental materials to be used, and match blood bio-compatibility test results with patients’ dental history before embarking on, at least major, dental procedures.